Contingent valuation: A new perspective - Felix Schläpfer (University of Zurich, Socioeconomic Institute, 2007)
After several decades of academic research on the contingent valuation (CV) method a consistent behavioral explanation of 'hypothetical bias' is still lacking. Based on evidence from economics, economic psychology and the political sciences, I propose an explanation that is based on two simple working hypotheses about respondent behaviour in contingent valuation surveys. The first hypothesis is that survey respondents are unable to form consistent preferences about unfamiliar goods unless the choice context offers reliable, informative cues that can be rationally exploited in simplified heuristics. The second hypothesis is that the probability and impact of strategic responses in dichotomous-choice questions about public goods depends on the extent to which the presented hypothetical costs differ from the actual costs. The literature on hypothetical bias is revisited in the light of these behavioral hypotheses. I find that the hypotheses are generally supported by the empirical data. Moreover, the hypotheses are able to explain several important empirical phenomena that previous research has not been able to explain. In particular, they solve the puzzle that pre-election polls, but not CV surveys, are able to predict actual referendum outcomes, and they explain why income effects on willingness to pay are lower in CV responses than in actual votes. If confirmed by further studies, the hypotheses will have important implications for future research and practice. First, the hypothetical costs presented in the dichotomous choice question should to be close enough to the actual costs to be credible to all respondents. This can be achieved by specifying the costs as a percentage (rather than absolute) change in taxes. Second, the respondents should be given the option to answer based on information about the positions of large parties and interest groups with known political orientation rather than based on the raw policy information. Theory and evidence suggest that this new survey paradigm largely eliminates the fundamental problems of the conventional stated preference methods.
Keywords: 330; behaviour; field experiments; hypothetical bias; incentive compatibility; information; preference formation; referendum; stated preferences; survey methodology; validity; voting behavior; Willingness to pay; Messung; Befragung; Offenbarte Präferenzen